Metagenome analysis from the sediment of river Ganga and Yamuna: In search of beneficial microbiome. - Bijay Kumar Behera; Biswanath Patra; Hirak Jyoti Chakraborty; Parameswar Sahu; Ajaya Kumar Rout; Dhruba Jyoti Sarkar; Pranaya Kumar Parida; Rohan Kumar Raman; Atmakuri Ramakrishna Rao; Anil Rai; Basanta Kumar Das; Joykrushna Jena; et al. (PLoS ONE, 2020)
Beneficial microbes are all around us and it remains to be seen, whether all diseases and disorders can be prevented or treated with beneficial microbes. In this study, the presence of various beneficial bacteria were identified from the sediments of Indian major Rivers Ganga and Yamuna from nine different sites using a metagenomic approach. The metagenome sequence analysis using the Kaiju Web server revealed the presence of 69 beneficial bacteria. Phylogenetic analysis among these bacterial species revealed that they were highly diverse. Relative abundance analysis of these bacterial species is highly correlated with different pollution levels among the sampling sites. The PCA analysis revealed that Lactobacillus spp. group of beneficial bacteria are more associated with sediment sampling sites, KAN-2 and ND-3; whereas Bacillus spp. are more associated with sites, FAR-2 and ND-2. This is the first report revealing the richness of beneficial bacteria in the Indian rivers, Ganga and Yamuna. The study might be useful in isolating different important beneficial microorganisms from these river sediments, for possible industrial applications.